2005
DOI: 10.1080/09593332608618501
|View full text |Cite
|
Sign up to set email alerts
|

Missing Aerobic-Phase Nitrogen: the Potential for Heterotrophic Reduction of Autotrophically Generated Nitrous Oxide in a Sequencing Batch Reactor Wastewater Treatment System

Abstract: Several biochemical pathways can induce nitrogen loss from aerated, aerobic wastewater treatment bioreactors. These pathways include "traditional" simultaneous nitrification-denitrification (SND) (i.e. autotrophic nitrification - heterotrophic denitrification), autotrophic denitrification, and anaerobic ammonia oxidation. An oxygen limitation, often expressed in terms of low dissolved oxygen (DO) concentration, is a common element of these pathways. The presented research investigated the effect of mixed liquo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Previous studies have also indicated that N isotope ratios might be useful indicators of microbial activity since nitrification generally has a much greater fractionation factor than denitrification (Pérez, 2005). Our results from Process A also indicate that both processes lead to N 2 O emissions, as previously reported by other investigations (Shiskowski and Mavinic, 2005; Ahn et al, 2010; Foley et al, 2010). Our measurements show that denitrification reactors have greater dissolved N 2 O concentrations than nitrification in Process A, probably because of aeration in the aerobic nitrification reactors that induces N 2 O stripping (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have also indicated that N isotope ratios might be useful indicators of microbial activity since nitrification generally has a much greater fractionation factor than denitrification (Pérez, 2005). Our results from Process A also indicate that both processes lead to N 2 O emissions, as previously reported by other investigations (Shiskowski and Mavinic, 2005; Ahn et al, 2010; Foley et al, 2010). Our measurements show that denitrification reactors have greater dissolved N 2 O concentrations than nitrification in Process A, probably because of aeration in the aerobic nitrification reactors that induces N 2 O stripping (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This reported sensitivity of N 2 O reductase to oxygen inhibition (e.g. Shiskowski and Mavinic, 2005), relative to the other reductase enzymes, induces heterotrophic N 2 O "generation", or more accurately allows its accumulation and emission, if the N 2 O reductase turnover rate is lower than the turnover rate of the previous enzymes (Wicht, 1996).…”
Section: Heterotrophic Bacteriamentioning
confidence: 94%
“…That research concluded that "for control of N 2 O emissions in the SBR, the aerobic fill mode could be an effective method" (Park et al, 2001). Shiskowski and Mavinic (2005) slowly pumped sodium acetate into an SBR during the aerobic phase, to simulate the existence of slowly degradable carbon in the solution and found significant reduction of N 2 O off-gas, via heterotrophic denitrification.…”
Section: The Effect Of Feed Patternmentioning
confidence: 99%
“…The N 2 O off-gas was monitored by an infrared N 2 O Monitor (Bacharach, N 2 O monitor 3010) (Shiskowski et al, 2005). Dissolved oxygen (DO), pH and oxidation reduction potential (ORP) probes were installed in each reactor and the monitoring data were recorded in a personal computer.…”
Section: Introductionmentioning
confidence: 99%